The Effect of the use of Augmented Reality (AR) Media on Student Learning Outcomes in the Subject of Science in Grade X at SMA Muhammadiyah Lempangang, Bajeng District, Gowa Regency - Muh Arif FIQRI; Nasir NASIR; Nurindah NURINDAH (International Journal of Environmental, Sustainability, and Social Science, 2025)
The main problem in this study is the effect of the use of Augmented Reality (AR) media on student learning outcomes in science subjects for class X at SMA Muhammadiyah Lempangang, Bajeng District, Gowa Regency. This study aims to determine whether there is an effect of the use of Augmented Reality (AR) media on student learning outcomes in science subjects for class X as intended. The type of research used in this study is a quantitative research type with an experimental method approach (pre-experiment), a one group pretest-posttest model. The analysis technique is in the form of Descriptive & Inferential statistics with the help of SPSS. The subjects in this study were 15 students of class X at SMA Muhammadiyah Lempangang, Bajeng District, Gowa Regency. Based on the results of the study, the results of inferential analysis with calculations using SPSS version 26, showed that the pretest and posttest data had met the normality test. It is a prerequisite test before conducting a hypothesis test. The pretest and posttest data were normally distributed because the p value ≥ α = 0.05. The inferential analysis shows that student learning outcomes are normally distributed (sig. > 0.05). The results also indicate that Augmented Reality (AR) media positively influences science learning outcomes of grade X students at SMA Muhammadiyah Lempangang. This is supported by a significance value of 0.000 < 0.05, indicating H0 is rejected and H1 is accepted.